Manajemen Media Sosial dalam Komunikasi Pemasaran Digital Instagram Yamie Panda Yogyakarta - Indra Wijanarko (Journal of Management and Bussines (JOMB), 2023)
Yamie Panda is a local business in the form of a restaurant that provides various yamie variants. In carrying out its activities, Yamie Panda uses several social media, one of which is Instagram. This research aims to find out how Instagram @yamiepanda social media is managed through the share, optimize, manage and engage stages. This research uses a descriptive method. The data collection techniques used were in-depth interviews, observation and literature study. From the research results, it is known that content management on Instagram social media @yamiepanda at the share stage begins with understanding Yamie Panda's target audience. In the optimize stage, monitoring is carried out to find out what is currently trending through hashtags. The management stage is carried out by creating a content schedule and data insight reports as an evaluation. At the engage stage, this is done by establishing relationships with influencers to increase exposure. Keywords: Instagram, Digital Marketing Communication, Social Media